Preferensi Konsumen Terhadap Keputusan Pembelian Varian Rasa Teazzi di Jakarta Selatan Dikaitkan dengan Karakteristik Konsumen - Ramadhani, Ingrid Putri; Deliana, Yosini (Universitas Galuh, 2026)
Teazzi is a Taiwanese milk tea brand that has expanded to various countries such as the United States, Indonesia, and Malaysia. Since its entry into the Indonesian market in 2021, Teazzi has continued to gain popularity, particularly in urban areas such as South Jakarta. This study involved 97 respondents who are Teazzi consumers making direct purchases at the Teazzi outlet in Pasaraya Blok M. The data analysis tool used was cross-tabulation (crosstab). The findings show that deep roast oolong milk tea is favored by (69.07%) of consumers, with (91,75%) those who purchased Teazzi directly at Pasaraya Blok M indicating their intention to repurchase the product. Consumers with positive preferences toward Teazzi’s purchase decisions are generally female, aged 21–25 years, hold a bachelor’s degree, work primarily as students, and have a monthly income of less than 1,000,000 rupiah.